(untitled) (Bangladesh Journal of Pharmacology, 2014)
The telomerase reverse transcriptase (TERT) sequence from Plasmodium falciparum provides valuable information for the design of specific anti-telomerase drugs. The present study deals with the interaction of pfTERT against berberine derivatives to derive novel analogues. Berberine intercalates DNA, thereby inhibits DNA synthesis and PfTERT. This indicated that P. falciparum telomerase might be a potential target for malaria chemotherapy. The nature of the interactions between A three-dimensional structural model of PfTERT was constructed using multiple sequence alignment and homology modeling procedures, followed by extensive molecular dynamics calculations. The analogues of berberine were successfully docked into the binding pocket of the protein. The hydrogen bonds were analyzed along with the binding energy was observed. The binding energy were found to be -8.36, -8.36, -8.23, -11.34, -10.51, -3.56, +186.20, -5.99, -1.10 and -7.48 in Kcal/mol with reference drugs. The least binding energy was found to be -11.34 Kcal/mol which determines that the most effective analogue. As a result this can be used as antiplasmodial drug.